2021
DOI: 10.1177/2374373521998839
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Communication Effectiveness and Patient Satisfaction

Abstract: This study assessed the correlation of 9 questions addressing communication effectiveness (the Communication Effectiveness Questionnaire [CEQ]) with other patient-reported experience measures (PREMs; satisfaction, perceived empathy) as well as patient-reported outcome measures (PROMs; pain intensity, activity tolerance) in patients with musculoskeletal illness or injury. In a cross-sectional study, 210 patients visiting an orthopedic surgeon completed the CEQ and measures of satisfaction with the visit, percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…As a result, heterogenous methods for measuring satisfaction are generally used 2 . Moreover, patient self-evaluation of satisfaction depends not only on the patient’s reading and understanding of the questions on satisfaction but also on the question number 20 and communication linked to examinations 21 . In addition, according to Herzberg’s motivational hygiene theory, patients are often unable to understand that satisfaction and dissatisfaction are not opposites 22 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, heterogenous methods for measuring satisfaction are generally used 2 . Moreover, patient self-evaluation of satisfaction depends not only on the patient’s reading and understanding of the questions on satisfaction but also on the question number 20 and communication linked to examinations 21 . In addition, according to Herzberg’s motivational hygiene theory, patients are often unable to understand that satisfaction and dissatisfaction are not opposites 22 .…”
Section: Discussionmentioning
confidence: 99%
“…We expect that if the association between independently assessed communication strategies and patient-rated clinician empathy was strong, we would have detected this, regardless of the notable ceiling effects of the empathy scale. Development of new patient-reported experience measures with limited ceiling effects is needed to better gauge the effect of improvement interventions on patient satisfaction, ratings of empathy, and trust in the clinician [32]. Third, we did not account for clinician personal factors.…”
Section: Limitationsmentioning
confidence: 99%
“…When I’ve studied satisfaction and experience in the past, I’ve found small correlations with symptoms of despair, health anxiety, and catastrophic thinking [2, 3, 11, 14, 18, 22, 25]. My research group found notable correlations with other measures of experience (trust, empathy, met expectations, communication effectiveness, and shared decision-making) [10, 12, 16-18, 20, 23, 24]. So notable, in fact, that I’m nearly ready to conclude, based on evidence to date, that the various measures of experience may all be measuring a single underlying construct that we currently refer to as “relationship.”…”
Section: Where Are We Now?mentioning
confidence: 99%